The Cauchy problem for parabolic equation over the field of p-adic numbers with impulse action - Luchko, V.M. (Carpathian Mathematical Publications, 2014)
The Cauchy problem for a parabolic equation with the impulse action is considered. Its solution is constructed and properties of the solution are studied above the field Q_p.